Semiotics of Advertising: Symbolic Strategies in Contemporary Media Discourse - Jalaboi, Elisabeta (Technium Social Sciences Journal, 2025)
Advertising represents one of the most powerful forms of contemporary communication, functioning not only as a persuasive instrument but also as a cultural text that encodes values, myths, and ideologies. This paper approaches advertising through the lens of semiotics, drawing on the classical frameworks of Saussure, Peirce, and Barthes, while integrating more recent perspectives from cultural studies and digital media theory. The study argues that advertising is a complex semiotic system that relies on iconic, indexical, and symbolic dimensions in order to produce meaning and to establish an emotional and cognitive connection with audiences. By analyzing selected case studies from global brands, european campaigns, and digital environments, the article demonstrates how advertising constructs cultural myths of consumption, happiness, and identity. The findings contribute to the growing field of applied semiotics by highlighting the interplay between denotation and connotation, the circulation of signs across media platforms, and the ideological underpinnings of consumer culture.